Healthcare provider interventions to support medication adherence: state-of-the-science overview - Crawshaw, Jacob; McCleary, Nicola (Frontiers in Pharmacology, 2025)
Medication adherence remains a global health issue and healthcare providers (HCPs) play an important role in supporting patients to adhere to treatment. This article provides a state-of-the-science overview of the evidence for: i) the effectiveness of HCP-delivered interventions on medication adherence outcomes; and ii) the types of implementation approaches targeting evidence-to-practice gaps among HCPs supporting medication adherence. Hundreds of randomized controlled trials and dozens of systematic reviews on the effectiveness of HCP-delivered interventions have been conducted to date. HCP-delivered interventions typically produce small-to-medium effect sizes on adherence outcomes, however, there is considerable heterogeneity in effects and few interventions that show promise are implemented into routine practice. Some key features of potentially effective HCP-delivered interventions include: moving beyond education-only, using multiple behaviour change strategies, tailoring interventions to different determinants of non-adherence, incorporating pharmacists and nurses to deliver interventions, providing ongoing support to patients, and addressing health system-level barriers and inequities. To improve the uptake of evidence into adherence-related clinical practice, it is likely that health systems must adapt to enable HCPs to better support adherence over time and in a patient-centered way. Such approaches include, improving routine screening of adherence issues, making adherence-related clinical guidelines more actionable, using routinely collected data to identify patients with adherence challenges, enhancing HCP incentivization models, and establishing quality indicators for adherence monitoring and support. Concepts and evidence from implementation science should be leveraged to support these types of system-level approaches to address evidence-to-practice gaps. In conclusion, despite an extensive evidence base for the effectiveness of HCP-delivered interventions - and a growing body of evidence for approaches targeting practice change among HCPs - we have identified several areas that could help advance the field. These include optimizing the content and delivery of adherence interventions, understanding how to implement effective strategies, and reaffirming the need for health system-level solutions.